Toward proof of concept of a One Health approach to disease prediction and control - Rabinowitz, P.M.; Kock, R.; Kachani, M.; Kunkel, R.; Thomas, J.; Gilbert, Jeffrey; Wallace, R.; Blackmore, C.; Wong, D.; Karesh, W.; Natterson, B.; Dugas, R.; et al. (Centers for Disease Control and Prevention, 2013)
A One Health approach considers the role of changing environments with regard to infectious and chronic disease risks affecting humans and nonhuman animals. Recent disease emergence events have lent support to a One Health approach. In 2010, the Stone Mountain Working Group on One Health Proof of Concept assembled and evaluated the evidence regarding proof of concept of the One Health approach to disease prediction and control. Aspects examined included the feasibility of integrating human, animal, and environmental health and whether such integration could improve disease prediction and control efforts. They found evidence to support each of these concepts but also identified the need for greater incorporation of environmental and ecosystem factors into disease assessments and interventions. The findings of the Working Group argue for larger controlled studies to evaluate the comparative effectiveness of the One Health approach.